Sleeve pneumonectomy for central non-small cell lung cancer: indications, complications, and survival - Eichhorn, Florian; Storz, Konstantina; Hoffmann, Hans; Muley, Thomas; Dienemann, Hendrik (The annals of thoracic surgery, 2013)
Background - Sleeve pneumonectomy is a challenging therapeutic strategy for patients with non-small cell lung cancer (NSCLC) invading the carina. The aim of this study was to illustrate common indications and individual concepts for surgery and to investigate oncologic outcomes and complications. - Methods - Sixty-four consecutive sleeve pneumonectomies were performed between September 2000 and November 2011. All patients had histologically proven central NSCLC. Data were retrospectively reviewed for indications, complications, and factors influencing long-term survival. - Results - Sixty-four patients underwent sleeve pneumonectomy for curative (n = 50, 78%) or palliative therapy (n = 14, 22%). Complete resection was achieved in 83%. Pathologic N2 disease was found in 41%. Complications occurred in 41%, with severe anastomotic problems in 8% of cases. Thirty-day mortality was 3% (n = 2). Outcome was significantly influenced by pathologic nodal status with 5-year survival rates of 70%, 35%, and 9% for N0, N1, and N2 subgroups, respectively. Patients with multilevel N2 disease and contraindications for chemotherapy or radiotherapy had a mean survival of 13 months after palliative surgery. - Conclusions - Sleeve pneumonectomy for central NSCLC invading the carina or proximal main bronchus can be performed with tolerable risk and encouraging survival rates in selected cases. Palliative sleeve pneumonectomy displays an option in the absence of alternative therapeutic strategies.
Gesehen am 08.01.2021